1992
DOI: 10.1093/ije/21.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Blood Prolactin Levels and the Risk of Subsequent Breast Cancer

Abstract: Between 1968 and 1976 a total of 5162 women volunteers were enrolled into a prospective study conducted on the Island of Guernsey. Up to February 1990 145 women subsequently developed breast cancer. Blood samples were taken at the time of enrollment and prolactin levels were known for 85% of the volunteers. In calculating the relationship between blood prolactin levels and subsequent breast cancer risk, women were excluded if they had a hysterectomy or an oophorectomy or had cancer at any site before enrollmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 0 publications
2
43
1
1
Order By: Relevance
“…A statistically significant higher risk of breast cancer was found in women who had PRL levels above 9.7 ng/ml (relative risk of 2.03 with a 95% CI (1.24-3.31)), even when several established breast cancer risk factors were controlled for. In another prospective study with 40 postmenopausal breast cancer patients, Wang et al found a positive but nonsignificant association between elevated PRL levels and the risk of developing breast cancer (Wang et al, 1992).…”
Section: Breast Cancermentioning
confidence: 96%
“…A statistically significant higher risk of breast cancer was found in women who had PRL levels above 9.7 ng/ml (relative risk of 2.03 with a 95% CI (1.24-3.31)), even when several established breast cancer risk factors were controlled for. In another prospective study with 40 postmenopausal breast cancer patients, Wang et al found a positive but nonsignificant association between elevated PRL levels and the risk of developing breast cancer (Wang et al, 1992).…”
Section: Breast Cancermentioning
confidence: 96%
“…High plasma prolactin levels were associated with a modestly increased risk of postmenopausal breast cancer [7,8]. About 95% of breast cancers expressed receptors for prolactin, meaning that they would be responsive to the stimulatory effect of prolactin [9][10][11]. However, in a study by Tworoger et al [12], a non significant positive relationship between prolactin levels and postmenopausal breast cancer was observed.…”
mentioning
confidence: 99%
“…1 The peptide hormone prolactin, essential in mammary development and lactation, is associated with an increased risk of breast cancer in both premenopausal 2 (Tworoger et al, 2006, submitted) and postmenopausal [3][4][5][6] women, likely through an increase in cell proliferation and inhibition of apoptosis. 7 Thus, prolactin may be one of potentially many hormonal links between reproductive risk factors and the incidence of breast cancer.…”
mentioning
confidence: 99%